A Força Emancipadora da Espiritualidade e da Mística no MST: Experiências Formadoras na vida dos(as) militantes como poder catalisador do movimento - Bedoya, Luis Eduardo Torres (2012)
The objective of the research is to ascertain and understand the emancipatory importance of spirituality and the mistica among the militants of the Landless Workers Movement (MST) specifically as formative experiences with implications in the construction of militancy and the development and consolidation of movement struggles. The purpose is to address the specificity of experiences of spirituality and of mistica in intentionality and meaning characteristic of the religious phenomenon. The research on mistica in the MST deal with, in general, the mistica activities scheduled on the institutional agenda of the MST, emphasizing its pedagogical, ideological, consciousness raising, mobilizing, political, cultural, identity creation, etc. importance. However, still missing is attention to the overlap of these activities with the personal experiences of religiosity, spirituality and mistica in their militants. This paper highlights these overlooked subjects in studies about the MST. It is an interdisciplinary study in the areas of (Auto) biography Research in Education, the Phenomenology of Religion and the Landless Workers Movement. The theoretical basis of the research brings together contributions from: Paulo Freire, Jorge Larrosa, Marie Christine Josso (formative experience and centrality of (auto) biographical research); Franco Ferrarotti (novelty, specificity and epistemological possibilities of the (auto) biographical method); Severino Croatto (phenomenological basis of the experiences of spirituality and mistica), Leonardo Boff (conceptualization and systematization of experiences of mistica in the MST). The methods used were: Narrative Thematic Interviews inspired in similar methods based in sociology, journalism and psychology; and Thematic Narrative Circles inspired in Paulo Freire’s cultural circles. The interview was applied to four militants, leaders of the MST-CE, between October 2009 and January 2010. Concurrently, three Narrative Circles were held featuring: settlers, militants, and young militants in training. The research showed that experiences of religiosity, spirituality and mistica are a part of the lives of members of the MST and are, in general, formative experiences that influence the quality of the militancy and the success of the movement struggles. The activities associated with the mistica in the MST is rooted in these experiences, a part of the movement since its inception, expressed in a synthesized and binding knowledge rooted in peasant culture, of the emancipatory spirituality which inspires and realizes the popular project for Brazil. The research has demonstrated the relevance of (auto) biographical knowledge to ascertain the essence of this type of experience, and to establish new understanding of social movements from the point of view of their subjects. The content of the experiences and knowledge gathered from interviews and the Circles Theme Narrative showed the extraordinary emancipatory strength of spirituality and mistica in the construction of militancy MST as a potential catalyst in the movement struggles.